2021
DOI: 10.1212/wnl.0000000000011108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rozanolixizumab in Moderate to Severe Generalized Myasthenia Gravis

Abstract: ObjectiveTo explore the clinical efficacy and safety of subcutaneous (SC) rozanolixizumab, an anti-neonatal Fc receptor humanized monoclonal antibody, in patients with generalized myasthenia gravis (gMG).MethodsIn this phase 2a, randomized, double-blind, placebo-controlled, 2-period, multicenter trial (NCT03052751), patients were randomized (1:1) in period 1 (days 1–29) to 3 once-weekly (Q1W) SC infusions of rozanolixizumab 7 mg/kg or placebo. In period 2 (days 29–43), patients were re-randomized to either roz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 24 publications
2
123
0
2
Order By: Relevance
“…Also of relevance, rozanolixizumab has been used in adult patients and has been found to be well tolerated with an acceptable safety profile. 20,21 Important questions, however, require further research. First, the timing of IgG transfer differs in humans and rodents; in the latter, it occurs mainly during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Also of relevance, rozanolixizumab has been used in adult patients and has been found to be well tolerated with an acceptable safety profile. 20,21 Important questions, however, require further research. First, the timing of IgG transfer differs in humans and rodents; in the latter, it occurs mainly during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach consists in treating autoimmune diseases with molecules from phage display libraries that target the Fc receptors. An example of this is the study carried out by Bril et al in which shown encouraging results in phase 3 trials by blocking the neonatal Fc receptor (FcRn) in myasthenia gravis (ClinicalTrials.gov Identifier: NCT03971422) with the therapeutic Rozanolixizumab (59). Furthermore, a peptide derived from a phage display library could inhibit IgGneonatal Fc receptor interaction reducing the IgG levels in vivo (60).…”
Section: Discussionmentioning
confidence: 99%
“…Severe headache, a prespecified study withdrawal criteria, resulted in withdrawal of three patients; overall, 57.1% rozanolixizumab‐treated patients reported headaches compared with 13.6% placebo. Infection rates were similar between placebo and treatment groups 87 . A subsequent confirmatory phase 3 study (Table 3) is currently recruiting AChR+ and MuSK+ gMG patients (NCT03971422).…”
Section: Recent and Ongoing Clinical Trials In Mgmentioning
confidence: 92%
“…Subjects received 3 weekly SC infusions of either 7 mg/kg of rozanolixizumab or placebo in dosing period 1, followed by re‐randomization to 4 mg/kg or 7 mg/kg of rozanolixizumab in period 2 and a subsequent 14‐week observation period. Total IgG and AChR antibody levels substantially reduced in the 7 mg/kg dosing group and MG‐ADL responder rate (>3‐point change) was higher in the treated (47.6%) compared with the placebo group (13.6%; P = .017) 87 . Severe headache, a prespecified study withdrawal criteria, resulted in withdrawal of three patients; overall, 57.1% rozanolixizumab‐treated patients reported headaches compared with 13.6% placebo.…”
Section: Recent and Ongoing Clinical Trials In Mgmentioning
confidence: 94%